The Development of Physics Education Game on Direct Current Electric Circuit for Learners - Ma'ruf, Jati Zen (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2021)
This study is the research of the development of physics education game application. This study has two purposes, namely to (1) developing multimedia for physics learning in the form of a physics education game on direct current electric circuits, (2) knowing the quality of educational game applications that have been produced according to experts, (3)knowing the user's (student's) response to the media of physics learning in the form of educational game applications related to direct current electrical circuit. The development procedure in this study refers to the Luther-Sutopo procedure consisting of the stage of concept, design, material collecting, assembly, testing, and distribution. Data collection techniques in the research in this study using a questionnaire. The research instrument in this study was a validation and assessment sheet which was adapted from the rubric for evaluating C. Stewart's educational game, student response sheets, and the game tester response sheet. Product validation and assessment uses a Likert scale with 4 scales and students' responses use the Guttman scale, while the game tester response sheet uses descriptive analysis. The results of this study are products in the form of simulation physics education game applications in direct current electric circuits, the results of the validation and assessment of material experts and media experts, the educational game application scored 3.8 and 3.3 in a very good category. The results of the user’s (student’s) response to the direct current electric circuit educational game application developed got an average score of 0.97 with the agreed category.